THE IMPACT OF JIIPE INTERNATIONAL PORT DEVELOPMENT ON THE SOCIAL ECONOMIC CONDITIONS OF THE COMMUNITY IN MANYAREJO VILLAGE, GRESIK REGENCY, INDONESIA - YANUAR, ADY FITRA; Kurniawati, Aida; Murtini, Sri; Rindawati, Rindawati (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2021)
Abstract: JIIPE International port construction in Manyarejo village, Manyar District is possible to have an impact on the residents' economy. Based on this, this study aims to determine the impact of development on the socio-economic conditions of the community. This type of research is descriptive quantitative. The research population is pond farmers, pond farmer laborers in Manyarejo village. The number of samples is 50 respondents consisting of 25 respondents who own pond land and and 25 respondents are pond farmers workers. Data were taken through questionnaires and interviews. Descriptive analysis was carried out on data on age, education, number of family dependents, livelihood, income, expenditure and productivity of pond land. The results showed that 1) The social conditions of the Manyarejo village community, especially shrimp, milkfish, and salt farmers changed by 44% become small traders, entrepreneurs, fishermen and employees, and 64% remain as pond farmers. 2) Community income from the aquaculture sector has decreased by 13% because agricultural land has been acquired and crop productivity decreased by 61%. Monthly income increased by 38% due to new livelihoods. Keywords: Port Development, Transfer of Land Functions, Social and Economic Conditions